Sistem Informasi Penggajian Karyawan Pada PT. Atlas Tata Citra Jambi - Aprilya, Vandacaroline; Zaenal Abidin, Dodo (LPPM Universitas Dinamika Bangsa, 2023)
The information system describes a system that has interrelated components such as collecting, processing, storing and distributing information to make a decision within an organization and can also be used as a consideration for decision making, coordination and control to help analyze the problem as a whole. One of the companies engaged in the distribution of building materials requires a computerized payroll system, namely PT. Atlas Tata Citra because there are still some problems at PT. Atlas Tata Citra is like managing employee salary data which still uses Microsoft Excel so that the process takes longer due to the large number of employees and data attachments for each employee must be processed and verified one by one. Another obstacle is filing payslips that are still manual, making it difficult for financial admins to find past data. Therefore authors conducted research on the analysis and design of payroll information systems at PT. The Tata Citra Atlas with the aim of the research that the author is conducting can be a consideration for companies to implement an information system in managing employee salary data that makes it easy to provide reports and payslips without requiring a long time. This research system modeling uses UML (Unified Modeling Language) including Use Case Diagrams, Activity Diagrams, Class Diagrams and prototype system development methods. The prototype design was carried out by the author using Figma.